Mechanisms of Convective Clustering During a 2‐Day Rain Event in AMIE/DYNAMO. (10th March 2020) - Cheng, Wei‐Yi; Kim, Daehyun; Rowe, Angela; Moon, Yumin; Wang, Shuguang
Abstract: Physical mechanisms that are key to observed convective clustering in 2‐day rain events are examined. Previous analysis of the 2‐day rain events during the Atmospheric Radiation Measurement Madden‐Julian Oscillation Investigation Experiment (AMIE)/Dynamics of the Madden‐Julian Oscillation (DYNAMO) field campaign data revealed two distinct phases of convective clustering. Using a cloud‐system‐resolving model, we perform a series of intervention experiments to investigate the underlying mechanisms for convective clustering in each phase. In the developing phase, in addition to previously emphasized processes such as the cold pool‐updraft interaction and moisture‐convection feedbacks, our results show that the vertical wind shear in the lower free troposphere is a critical factor for convective clustering. Stronger lower free‐tropospheric wind shear increases the entrainment of environmental air into updrafts and prevents convective clouds from being omnipresent. This result suggests that stronger vertical wind shear in the lower free troposphere can help spatially organize the convection, even for non–squall‐line‐type convective systems. In the decaying phase, the cold pool‐updraft interaction becomes less effective in aggregating convective clouds because the boundary layer is widely cooled by stratiform precipitation. Instead, the mesoscale downdraft driven by the stratiform precipitation becomes the dominant factor to maintain the relatively aggregated convection. Additionally, removing horizontal variations in radiative heating has no impact on convective clustering on this 2‐day time scale, even in the decaying phase when stratiform clouds are widespread. The implication of these results for improving the representation of mesoscale convective organization in convection schemes is discussed. Plain Language Summary: Tropical thunderstorms often cluster together. Studies have suggested that the degree to which the tropical thunderstorms are clustered impacts Earth's energy balance and water cycle, as well as extreme precipitation events. However, the processes controlling the spatial distribution of the thunderstorms are poorly understood and are not properly represented in most computer models for weather and climate prediction. This study aims to understand the processes that control the organization (i.e., clustering) of thunderstorms. We target an observed 2‐day rain event over the tropical ocean and investigate its organization processes by conducting a series of numerical experiments that are designed to test selected physical mechanisms. We show that the key organization processes may differ depending on the life stage of the rain event. During the intensifying stage where thunderstorms are continuously forming, the moisture distribution and the environmental vertical wind shear act to confine the thunderstorms within the moist regions. Changes in boundary layer temperature driven by the thunderstorm further trigger additional thunderstorms nearby, leading to more organized thunderstorms. During the decaying stage where thunderstorms are gradually dissipating, the remaining clustered thunderstorms will drive circulations that help maintain the clustered thunderstorms. Key Points: Stronger lower free‐tropospheric vertical wind shear aids convective clustering Evaporation of stratiform precipitation helps maintain clustered convective systems Radiative feedback plays no role in clustering convection during the 2‐day rain event